Roles of pectin in biomass yield and processing for biofuels - Xiao, Chaowen; Anderson, Charles T. (Frontiers in Plant Science, 2013)
Pectin is a component of the cell walls of plants that is composed of acidic sugar-containing backbones with neutral sugar-containing side chains. It functions in cell adhesion and wall hydration, and pectin crosslinking influences wall porosity and plant morphogenesis. Despite its low abundance in the secondary cell walls that make up the majority of lignocellulosic biomass, recent results have indicated that pectin influences secondary wall formation in addition to its roles in primary wall biosynthesis and modification. This mini-review will examine these and other recent results in the context of biomass yield and digestibility and discuss how these traits might be enhanced by the genetic and molecular modification of pectin. The utility of pectin as a high-value, renewable biomass co-product will also be highlighted.